Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1136/bmjopen-2017-016224
|View full text |Cite
|
Sign up to set email alerts
|

SSRI antidepressant use potentiates weight gain in the context of unhealthy lifestyles: results from a 4-year Australian follow-up study

Abstract: ObjectiveTo examine the association between antidepressant use and weight gain, as well as the interaction with lifestyle factors.DesignLongitudinal study.Setting and participantsWe used data from 2334 adults from two stages (4.4 years apart) of the North West Adelaide Health Study, including validated diet and lifestyle questionnaires, measured body weight and linked pharmaceutical prescription data.Main outcome measuresBody weight change.Results188 (8.1%) participants had a mean annual number of 1–2 antidepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 19 publications
0
34
1
Order By: Relevance
“…The relation between depression symptoms and health behaviours that might contribute to weight gain is also a relevant concern. 30 …”
Section: Discussionmentioning
confidence: 99%
“…The relation between depression symptoms and health behaviours that might contribute to weight gain is also a relevant concern. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Among the antidepressants studied, Mirtazapine, Fluoxetine, Citalopram, Escitalopram, Sertraline, Paroxetine, Trazodone, Venlafaxine, and Duloxetine had a positive association with weight gain. However, some studies evaluating TCAs did not show association, but several studies with Bupropion showed weight loss …”
Section: Resultsmentioning
confidence: 99%
“…In two studies, the number of women was more than double the number of men, because a greater proportion of women are affected by depression. Regarding the duration of the studies, we identified studies of less than 5 years, and others with more than 10 years of follow‐up …”
Section: Resultsmentioning
confidence: 99%
“…Significant improvements were seen in some health behaviours (emotional eating, cognitive restraint, and total physical activity; Table 3), and trends toward improvements seen in others (uncontrolled eating [p = .127] and discretionary food intake [p = .084]). Physical activity, nutrition, and eating behaviours are confounding variable that may prevent weight loss (particularly when accompanied by an unhealthy lifestyle) is antidepressant therapy [23,24], and 11 of our 18 subjects were taking antidepressants during the program. While our current trial was not designed nor powered to answer the question of whether antidepressant status affects weight loss during/after the intervention, larger future trials can incorporate this question into their design.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviourally, a person who experiences depression may reduce their activity and increase their intake of comfort foods, resulting in weight gain and elevated cortisol, which in turn promotes appetite (especially for less healthy foods) and further weight gain [19,21,22]. Antidepressants may also be associated with increased appetite and weight gain, particularly in the context of unhealthy lifestyles [23,24]. Cognitively, negative thinking patterns and low self-worth contribute to distress and unhelpful behavioural responses.…”
Section: Introductionmentioning
confidence: 99%